Global Development Finance 2011 : External Debt of Developing Countries - World Bank (2012)
The World Bank's Debtor Reporting System (DRS), from which the aggregates and country tables presented in this report are drawn, was established in 1951. The debt crisis of the 1980s brought increased attention to debt statistics and to the World debt tables, the predecessor to Global development finance. Now the global financial crisis has once again heightened awareness in developing countries of the importance of managing their external obligations. International capital flows to the 128 developing countries reporting to the World Bank Debtor Reporting System (DRS) fell by 20 percent in 2009 to $598 billion (3.7 percent of Gross National Income (GNI), compared with $744 billion in 2008 (4.5 percent of GNI) and a little over half the peak level of $1,111 billion realized in 2007. Private flows (debt and equity) declined by 27 percent despite a rebound in bond issuance, portfolio equity flows, and short-term debt flows. Both foreign direct investment (FDI) flows and bank lending fell precipitously. By contrast, the net inflow of debt-related financing from official creditors (excluding grants) rose 175 percent as support was stepped up to low- and middle-income countries severely affected by the global financial crisis.